THE WORKING ENVIRONMENT INVOLVES US ALL - Vergilică HARALAMBIE; Eugenia BULBOACĂ; Oana Roxana CHIVU; Alina FATU,; Daniel BADEA (Fiabilitate şi Durabilitate)
: The document presents the practical exercise to support employers in successfully managing and controlling OH&S activity to prevent risks associated with the working environment, increasing employee productivity and improving OH&S in line with Romanian and EU legislation. The experiment presented consists in determining the degree of compliance of OH&S with legal requirements, implementing the recommended measures, questioning the industrial working environment, interpretation and comparison of results. After implementation of measures at the organization there were increases in the level of compliance and security, the decrease in the level of risk. TIMS survey included respondents grouped into four categories: T(18-24 years), I (25-34 years), M (35-49 years), S (50-64 years). Useful advice for employers on: working meetings, choosing the right work environment for employees, personalizing the work environment, managing time and working mode, and highlighting the performance of the organization.